Global change and future earth the geoscience perspective - Alverson, Keith; Beer, Tom; Li, Jianping (Cambridge University Press, 2018)
Global Change and Future Earth is derived from the work of several programs of the International Union of Geodesy and Geophysics (IUGG). It demonstrates how multi- and inter-disciplinary research outputs from the geoscience community can be applied to tackle the physical and societal impacts of climate change and contribute to the Future Earth programme of the International Council for Science. The volume brings together an international team of eminent researchers to provide authoritative reviews on the wide-ranging ramifications of climate change spanning eight key themes: planetary issues; geodetic issues; the Earth's fluid environment; regions of the Earth; urban environments; food security; and risk, safety and security; and climate change and global change. Covering the challenges faced by urban and rural areas, and in both developed and developing counties, this volume provides an important resource for a global audience of graduate students and researchers from a broad range of disciplines, as well as policy advisors and practitioners.